Studies of autofluorescence in experimentally induced cerebral necrosis in pigs - Lee, J. Y.; Little, P. B. (Sage Publications, 1980)
Lesions of cerebrocortical necrosis experimentally induced in pigs by transcalvarial freezing with liquid nitrogen were slightly fluorescent 48 hours after surgery. Fluorescence increased greatly thereafter and was most marked grossly under ultraviolet illumination with a wavelength of 366 nm at 7 days. Fluorescence of the necrotic focus persisted up to 35 days after surgery. Detection of cerebrocortical necrosis by ultraviolet illumination of fresh specimens during gross inspection is useful in determining the extent and distribution of lesions. This would aid more accurate selection of brain sections for histological examination in various encephalopathies.